THE MODERATING EFFECT OF CORPORATE GOVERNANCE ON THE RELATIONSHIP BETWEEN CAPITAL STRUCTURE AND COMPANY PERFORMANCE - Jong, Steven; Imelda, Elsa; Sastrasasmita, Emillia (Graduate Program of Universitas Tarumanagara, 2025)
The objective of this research is to identify the impact of corporate governance as moderator variables on the capital structure and company performance relationship within non-cyclical consumer companies listed on the Indonesia Stock Exchange from 2021 to 2023. This study uses secondary data using 54 samples selected through the purposive sampling method and processed using the E-views 12 program. The results obtained show that both long-term and short-term debt-to-total assets ratios have a significant negative impact on ROE. However, corporate governance factors like Board Size, Commissioner Size, and shareholder size cannot moderate this relationship.